Economic integration and migration: The Mexico-US case - Philip Martin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper explains the evolution and effects of Mexico-US migration, and highlights the NAFTA approach to economic integration, viz., free up trade and investment while stepping up efforts to prevent unauthorized migration. The European Union approach is different: provide aid first, and later free up trade and migration in the expectation that moves toward convergence will ensure minimal migration because trade has become a substitute for migration. The paper concludes that NAFTA will reduce unwanted Mexico-US migration in the medium to long term, and that different initial conditions in Europe mean that there will be relatively little east-west migration when nationals of new entrant EU members achieve freedom of movement.
Keywords: F22; R23; 330; Mexico-US migration; international migration; Internationale Wanderung; NAFTA-Staaten; Mexiko; USA